2021
DOI: 10.1186/s12884-021-04314-2
|View full text |Cite
|
Sign up to set email alerts
|

Choline intake and associations with egg and dairy consumption among pregnant women attending a high-risk antenatal clinic in South Africa: the NuEMI study

Abstract: Background The importance of adequate choline intake during pregnancy has been well documented, but low intake is common. Total choline intake, main food sources of choline, as well as associations between choline intake and egg and dairy consumption were determined in a sample of pregnant women attending the high-risk antenatal clinic at a regional hospital in Bloemfontein, South Africa. Methods A cross-sectional study design was used. Trained fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…23 - 25 Dietary intake was determined for the previous 28 days, and nutrient intake values were divided by 28 to calculate daily intake. 26 Daily or weekly (28 days intake divided by 4) intake of relevant food groups included in the MeDAS 14-item questionnaire 14 were extracted from the QFFQ. The MeDAS 14 was adapted for the current study on pregnant women to a 13-item questionnaire; the question on alcohol (wine) was omitted.…”
Section: Methodsmentioning
confidence: 99%
“…23 - 25 Dietary intake was determined for the previous 28 days, and nutrient intake values were divided by 28 to calculate daily intake. 26 Daily or weekly (28 days intake divided by 4) intake of relevant food groups included in the MeDAS 14-item questionnaire 14 were extracted from the QFFQ. The MeDAS 14 was adapted for the current study on pregnant women to a 13-item questionnaire; the question on alcohol (wine) was omitted.…”
Section: Methodsmentioning
confidence: 99%
“…For several vital nutrients, eggs can contribute a large portion of the Recommended Daily Allowance (RDA) or adequate intake (AI) for pregnant and lactating women; for instance, two 50-g eggs provide between 20% and 35% of the AI/ RDA for vitamin A, riboflavin, pantothenic acid, vitamin B12 and phosphorus for pregnant and lactating women, and more than 18% of the RDA for protein and 50% of the AI/RDA for choline and selenium (Lutter et al, 2018). Studies in the US and South Africa show that pregnant mothers had choline intakes below the AI, and this was associated with lower egg and dairy intake (Wallace and Fulgoni, 2017;Robb et al, 2021). Wallace and Fulgoni (2017) reported that meeting the AI for choline without egg consumption or a dietary supplement is challenging, even in the US.…”
Section: Pregnant and Lactating Womenmentioning
confidence: 99%
“…The current study extracted the women's sociodemographic data, gestational body mass index (GBMI) dietary data and birth outcomes of their infants. Dietary data in the NuEMI study were collected with a 28-day quantitative food frequency questionnaire (QFFQ) (techniques and validity of the QFFQ in this population is discussed in detail elsewhere [19]), and a single 24-hour recall administered during the same interview.…”
Section: Data Collectionmentioning
confidence: 99%